KONFLIK INDONESIA BELANDA TERHADAP PREBUTAN KEKUASAAN IRIAN BARAT - aprilia iva swastika (LP4MK STKIP PGRI Lubuklinggau, 2021)
The conflict between Indonesia and the Netherlands over the seizure of West Irian occurred in 1949. This problem occurred due to the abundant mining wealth in West Irian that would be exploited by the Dutch on the grounds that they wanted to disarm Japanese troops in Indonesia. By asking the UN for assistance, this problem will be resolved with the KMB agreement. Foreign countries like America also help politically and economically as well as help to finance military equipment and also help increase military troops. During the year the KMB agreement was signed, West Irian was not handed over to Indonesia. Then the Indonesian government at that time fought physically with the formation of TRIKORA, the New York Battle, and PAPERA.